WAHDAT AL-WUJUD DAN IMPLIKASINYA TERHADAP INSAN KAMIL - Adenan Adenan; Tondi Nasution (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2020)
Sufism is one of the sciences that can help the realization of quality human beings. The science of Sufism is a link with other sciences with the outer side that is like a body and spirit that cannot be separated. The science is also called inner science as Shaykh al-Manawi's opinion in explaining the Prophet's hadith: 'Science is of two kinds, the knowledge that exists in the heart, that is useful knowledge and the science spoken by the tongue is the science of hujjah / law, or bahin science comes out from heart and science dhahir it comes out of the tongue. Based on the above, in its application, Sufism has a variety of style concepts and understanding, one of which is wahdatul wujud. Wahdatul Wujud is an expression consisting of two words, Wahdah and al-Wujud. Wahdat means alone, single or unity while al-wujud means. Thus wahdahtul wujud means the unity of being. As a result of this diversity, wahdatul wujud became a controversial term among Muslims. For some they are manifested, in particular, and Sufism in general, is a form of deviation from pure Islamic teachings. Others reject wahdatul being and consider it partly something dangerous to Muslims, especially those who are laymen, while accepting Sufism as an integral part of Islam. But for others wahdatul wujud is the culmination of mystical experience in Islam which in some traditions of the Prophet referred to as ihsan. Departing from the above problems, will be discussed further about Wahdad Al Wuju and Insan Kamil to provide a clear and clear picture of Sufism. In this case the author summarizes in the title "Wahdat Al-Wujud and Its Implications for Kamil's People".Keywords: Wahdat Al-Wujud, Kamil's People.